Spatial and Temporal Patterns in Atmospheric Deposition of Dissolved Organic Carbon. Issue 10 (17th October 2022) - Liptzin, Daniel; Boy, Jens; Campbell, John L.; Clarke, Nicholas; Laclau, Jean‐Paul; Godoy, Roberto; Johnson, Sherri L.; Kaiser, Klaus; Likens, Gene E.; Karlsson, Gunilla Pihl; Markewitz, Daniel; Rogora, Michela; et al.
Abstract: Atmospheric deposition of dissolved organic carbon (DOC) to terrestrial ecosystems is a small, but rarely studied component of the global carbon (C) cycle. Emissions of volatile organic compounds (VOC) and organic particulates are the sources of atmospheric C and deposition represents a major pathway for the removal of organic C from the atmosphere. Here, we evaluate the spatial and temporal patterns of DOC deposition using 70 data sets at least one year in length ranging from 40° south to 66° north latitude. Globally, the median DOC concentration in bulk deposition was 1.7 mg L −1 . The DOC concentrations were significantly higher in tropical (<25°) latitudes compared to temperate (>25°) latitudes. DOC deposition was significantly higher in the tropics because of both higher DOC concentrations and precipitation. Using the global median or latitudinal specific DOC concentrations leads to a calculated global deposition of 202 or 295 Tg C yr −1 respectively. Many sites exhibited seasonal variability in DOC concentration. At temperate sites, DOC concentrations were higher during the growing season; at tropical sites, DOC concentrations were higher during the dry season. Thirteen of the thirty‐four long‐term (>10 years) data sets showed significant declines in DOC concentration over time with the others showing no significant change. Based on the magnitude and timing of the various sources of organic C to the atmosphere, biogenic VOCs likely explain the latitudinal pattern and the seasonal pattern at temperate latitudes while decreases in anthropogenic emissions are the most likely explanation for the declines in DOC concentration. Plain Language Summary: Dissolved organic carbon (DOC) is ubiquitous in precipitation. However, the geographic and temporal patterns in terrestrial ecosystems are not well established. We analyzed 70 data sets of DOC from rainfall collectors sampled for at least a year to examine these patterns and relate them to possible sources of the carbon. The combination of higher concentrations of DOC and more precipitation resulted in greater DOC deposition at low latitude sites. Some sites had strongly seasonal patterns in DOC concentration while others had similar concentrations year round. The most noticeable seasonal pattern was that the mid‐latitude sites had the highest concentrations during the summer months. The latitudinal and seasonal patterns of DOC deposition best matched with the pattern of emissions of organic compounds from plants to the atmosphere suggesting plant emissions are the dominant source of DOC to ecosystems. The temporal trends from sites with at least 10 years of data suggest declining DOC concentrations, especially in the mid‐latitudes. These declines are consistent with declines in anthropogenic emissions of organic compounds to the atmosphere over this time period. It is essential to document the patterns and changing amounts of DOC and other compounds in precipitation to understand the effects on terrestrial ecosystems. Key Points: Many sites have strong seasonal patterns in the concentration of carbon in precipitation Low latitudes have the highest carbon deposition because of significantly higher concentrations of carbon and greater precipitation The seasonal, temporal, and latitudinal patterns of carbon in atmospheric deposition are most consistent with biogenic emissions